2020
DOI: 10.3390/su12030997
|View full text |Cite
|
Sign up to set email alerts
|

Showcasing Relationships between Neighborhood Design and Wellbeing Toronto Indicators

Abstract: Cities are the keystone landscape features for achieving sustainability locally, regionally, and globally. With the increasing impacts of urban expansion eminent, policymakers have encouraged researchers to advance or invent methods for managing coupled human–environmental systems associated with local and regional sustainable development planning. Although progress has been made, there remains no universal instrument for attaining sustainability on neither regional nor local planning scales. Previous sustaina… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 94 publications
0
2
0
Order By: Relevance
“…Based on this ranking, it was possible to conduct a qualitative evaluation of each of the Resilience Strategies and to compare them to one another in order to identify the contribution of each to adaptation to climate change. Thus, the aforementioned determinants function as essential qualitative indicators of resilience, adaptation, sustainability, and planning initiatives [5,6,35]. They can also be used for the evaluation of other strategies.…”
Section: Methodsmentioning
confidence: 99%
“…Based on this ranking, it was possible to conduct a qualitative evaluation of each of the Resilience Strategies and to compare them to one another in order to identify the contribution of each to adaptation to climate change. Thus, the aforementioned determinants function as essential qualitative indicators of resilience, adaptation, sustainability, and planning initiatives [5,6,35]. They can also be used for the evaluation of other strategies.…”
Section: Methodsmentioning
confidence: 99%
“…Although this trend is likely not going to slow down, it shows that there is a need to find ways to mitigate the impact our urban centres have on the natural environment. The other metrics that should be addressed inn future research is COHESION, which has been identified and validated through multiple studies already at global and local scales (Shaker et al, 2020;. There is an importance to also take this metrics beyond the urban fabric and look at COHESION throughout the natural environment as well, which has been seen as an important metric at local scales (Meerow & Newell, 2017), but its importance must be explored at a macroscale landscapes along with other landscape metrics as well.…”
Section: Future Direction Of Researchmentioning
confidence: 99%
“…With the growing quantity of higher resolution geospatial data, future research can be improved by including more criteria or using more current data at a finer scale. For instance, these could include landscape ecology metrics that capture additional ecosystem goods and services such as habitat physical connectedness, biodiversity, and recreation [84,85]. Progressing this research to the next level using the aforementioned ideas will help to meet the Ontario Ministry of Natural Resources and Forestry goals, which call for a reinstatement of wetland area and function to landscapes where loss has been the greatest.…”
Section: Recommendations and Future Considerationsmentioning
confidence: 99%